Women's Impact on Islamic Heritage: Analyzing the Contribution of Female Companions in Hadith Narrations in Basrah: Dampak Perempuan pada Warisan Islam: Menganalisis Kontribusi Sahabat Perempuan dalam Periwayatan Hadis di Basrah - Safitri, Ohza Ikmaya; bin Maswar, Muhammad Syafik (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Objectives: The role of women in the transmission of hadith and the early formation of Islam is of significant importance. This article aims to examine the contribution of female friends in Basrah in the transmission of hadith. Methodology: This research employs qualitative methods with a historical approach to analyze the contribution of female companions in the narration of hadith in Basrah. The data was obtained through literature studies and using agency theory to understand women's perspectives as agents of change. The main results: there were nine female companions in Basrah who narrated hadith with various themes; law, morals, muamalah, worship, tarikh, and aqidah. The theme of law and morals dominates. Nusaibah bint al-Ḥāriṡ is the only female companion known to have narrated hadith with various themes. This research contributions that female companions played an important role in the transmission of hadith and the teaching and spread of Islamic teachings in Basrah. Women like Nusaibah bint al-Ḥāriṡ played key roles in various aspects of Islamic life. Conclusion: Women played a significant role in the transmission of hadith and the early formation of Islam. Their involvement contributed to the perfection of the teachings of the Prophet Muhammad.